Amaranth: distribution and morphological diversity of the genetic resource in parts of the Mayan region (southeast of Mexico, Guatemala and Honduras) - Aguilera-Cauich, Erick A.; Solís-Fernández, Karen Z.; Ibarra-Morales, Ariadna; Cifuentes-Velásquez, Rolando; Sánchez-del Pino, Ivonne (Instituto de Ecología, A.C., 2020)
Background and Aims: Amaranth is of worldwide interest for its nutritional value as a vegetable and grain. The principal cultivated species used as grain are Amaranthus caudatus, A. cruentus and A. hypochondriacus. Two accepted hypotheses about the origin of A. cruentus consider A. hybridus as its ancestor. The objectives of this study are 1) to report the updated distribution and frequency of A. cruentus and A. hybridus in southeastern Mexico, Guatemala, and Honduras and 2) to assess their morphological diversity, using floral and fruit characters of both species in Mexico and Guatemala.Methods: The information gathered from 147 herbarium examples was used to update the distribution and determine the frequency of A. cruentus and A. hybridus in the study area, possible area of domestication. Morphological diversity was determined using 22 morphological characters related to pistillate flowers and fruits by conducting a multivariate analysis of main components in a sampling of 15 specimens of A. cruentus and 31 of A. hybridus from Guatemala and southeastern Mexico.Key results: The main distribution of A. cruentus was shown in Guatemala, and of A. hybridus in Mexico. The accumulated variation in the first three principal components was 58% for both species. The morphological variation for both species was mainly associated with characters related to the internal and external sepals. The principal components analysis graph showed wide morphological variation in A. cruentus and A. hybridus regardless of their geographical distribution in both cases.Conclusions: The geographical distribution of A. cruentus in Mexico is wider than previously reported. Diversity was described using morphological characters of pistillate flowers and fruits for A. cruentus and A. hybridus.